Analysis of Histopathological Findings in Endometrium of Peri-Menopausal Women Presenting with Dysfunctional Uterine Bleeding - Asim Iqbal Qureshi, Shazia Shafi, Maria Khan, Ayesha Munir, Bazgha Sahar, Abeera Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To analyze histopathological findings in endometrium of peri-menopausal women presenting with dysfunctional uterine bleeding at a tertiary care hospital of South Punjab, Pakistan. Study Design: Cross sectional study. Place and Duration of the Study: The Department of Obstetrics & Gynecology, Bakhtawar Amin Trust Teaching Hospital, Multan, Pakistan from April 2021 to March 2022. Material Methods: During the study period, a total of 141 peri-menopausal women (aged 41 to 55 years) who presented with abnormal vaginal bleeding and underwent diagnostic endometrial curettage for histological analysis were included. A detailed history and careful systemic and pelvic examinations were performed. Endometrial tissue was obtained during dilatation & curettage (D&C) and preserved in 10% formaline and subjected for histopathologic analysis. Clinical and histological information of all subjects were recorded. Results: In a total of 141 women, mean age was calculated to be 47±7 years. Except 24 (17.0%) patients who were already menopausal, 67 (47.5%) patients had normal length of menstrual cycle. Nearly half of the patients had normal histology of the endometrium. Simple hyperplasia was present in 18 (12.8%) and complex hyperplasia was in 10 (7.1%). Only 2 cases (1.4%) each of atypical endometrial hyperplasia and endometrial carcinoma were reported on the histology. Five patients (3.5%) had decidual change in the endometrium, which was mostly due to the prior intake of progestogens as part of medical therapy. Inflammation of endometrium was not uncommon and 19 (13.5%) had presence of inflammatory cells in the endometrium. Conclusion: Peri-menopausal women with abnormal uterine bleeding should undergo diagnostic endometrial curettage to rule out the possibility of malignant or pre-malignant pathology. In perimenopausal patients, endometrial biopsy and other methods of detecting endometrial hyperplasia or carcinoma must be considered early in the investigation. Keywords: Dysfunctional uterine bleeding endometrium, histopathology, peri-menopausal,